How does hiring part time employee facilities kitchen operation in the hotel industry; Case study of Philea Hotel (resort) & Majestic Hotel (city hotel) / Azlan Abdullah and Faizal Azrin Abdullah - Abdullah, Azlan; Abdullah, Faizal Azrin (2017)
Human capital is considered the most essential part of an organization. The significance and contribution of human capital is implicated through the performance and sustainability of an organization and an industry as a whole scenario that been bond for the last few decades. As in the hotel industry, there are limitations on hiring full time staff due to its normal operation and cost effective. As it comes to seasonal occasion, hotels are the place where people go to stay, dine and attend the events. Management may see the forecast of upcoming events and how to overcome the situation. They usually have the plan on how to make the operation runs smoothly. Hiring part time workers is to help the full-time workers doing their job in a busy situation. The task is double or triple than the normal situation. It needs people to support and work together to achieve the goals. As part of the expansion and due to shortage of employee, organizations are known to engage in part time employment services. This allows the organization fill the gaps that exist in the manpower in order to fulfill the smoothness of any events and to keep up good name of the organization. Employing part time workers is the short-term solution rather than fully utilizing the present permanent staff. Part time employment is known to aid organization to boost it operation and in turn to aid in the increase profits for the hotels. By employing part time workers, tasks can be easily done faster and may produce more volume of the products. Chefs will have less burden to completing the job done and may shortened the time for doing preparation and cooking.